Process evaluation of a complex workplace intervention to prevent musculoskeletal pain in nursing staff: results from INTEVAL_Spain - Mercè Soler-Font; José Maria Ramada; Antoni Merelles; Anna Amat; Carmen de la Flor; Olga Martínez; Claudia Palma-Vasquez; Consuelo Sancho; Pilar Peña; Ute Bültmann; Sander K. R. van Zon; Consol Serra (BMC, 2021)
Abstract Background INTEVAL_Spain was a complex workplace intervention to prevent and manage musculoskeletal pain among nursing staff. Process evaluations can be especially useful for complex and multifaceted interventions through identifying the success or failure factors of an intervention to improve the intervention implementation. Objectives This study performed a process evaluation of INTEVAL_Spain and aimed to examine whether the intervention was conducted according to the protocol, to investigate the fulfilment of expectations and the satisfaction of workers. Methods The intervention was a two-armed cluster randomized controlled trial and lasted 1 year. The process evaluation included quantitative and qualitative methods. Quantitative methods were used to address the indicators of Steckler and Linnan's framework. Data on recruitment was collected through a baseline questionnaire for the intervention and the control group. Reach and dose received were collected through participation sheets, dose delivered and fidelity through internal registries, and fulfilment of expectations and satisfaction were collected with two questions at 12-months follow-up. Qualitative methods were used for a content analysis of discussion groups at the end of the intervention led by an external moderator to explore satisfaction and recommendations. The general communication and activities were discussed, and final recommendations were agreed on. Data were synthesized and results were reported thematically. Results The study was performed in two Spanish hospitals during 2016-2017 and 257 workers participated. Recruitment was 62 and 51% for the intervention and the control group, respectively. The reach of the activities ranged from 96% for participatory ergonomics to 5% for healthy diet. The number of sessions offered ranged from 60 sessions for Nordic walking to one session for healthy diet. Fidelity of workers ranged from 100% for healthy diet and 79% for participatory ergonomics, to 42 and 39% for Nordic walking and case management, respectively. Lowest fidelity of providers was 75% for case management and 82% for Nordic walking. Fulfilment of expectations and satisfaction ranged from 6.6/10 and 7.6/10, respectively, for case management to 10/10 together for the healthy diet session. Discussion groups revealed several limitations for most of the activities, mainly focused on a lack of communication between the Champion (coordinator) and the workers. Conclusions This process evaluation showed that the implementation of INTEVAL_Spain was predominantly carried out as intended. Process indicators differed depending on the activity. Several recommendations to improve the intervention implementation process are proposed. Trial registration ISRCTN15780649 .